Precision Recovery in Interventional Pulmonology: A Randomized Controlled Trial Comparing Propofol Target-Controlled Infusion versus Sevoflurane Inhalation on Emergence Kinetics and Hemodynamic Stability - Putra Setiawan; Dino Irawan; Tengku Addi Saputra (HM Publisher, 2026)
Background: Achieving a rapid and high-quality recovery is a cornerstone of modern procedural sedation, particularly in high-turnover ambulatory bronchoscopy suites. Patients presenting for bronchoscopy often exhibit significant pulmonary pathology, including ventilation-perfusion mismatch, which may theoretically impede the alveolar washout of volatile anesthetics. This study aimed to compare the recovery kinetics, hemodynamic stability, and adverse event profiles of Propofol Target-Controlled Infusion (TCI) utilizing the Schnider model versus standard Sevoflurane inhalational anesthesia. Methods: In this single-blind, prospective, randomized controlled trial, 36 adult patients (ASA I–III) undergoing elective flexible bronchoscopy were recruited. Participants were randomly allocated to receive either Propofol TCI (Group P; Schnider model, target effect-site concentration 4–6 micrograms/mL) or Sevoflurane (Group S; 2 volume percent). The depth of anesthesia was strictly titrated using Bispectral Index (BIS) monitoring to maintain a range between 40 and 60. The primary outcome was recovery time, defined as the duration from anesthetic discontinuation to eye-opening upon verbal command. Secondary outcomes included intraoperative hemodynamic stability (Mean Arterial Pressure and Heart Rate), BIS values at the moment of emergence, and the incidence of postoperative nausea and vomiting (PONV). Results: The Propofol TCI group demonstrated a statistically significant reduction in recovery time (9.72 ± 1.52 minutes) compared to the Sevoflurane group (12.11 ± 1.49 minutes; p < 0.001). Procedural duration was comparable between groups (p = 0.412), eliminating surgical time as a confounding variable. Group P exhibited superior hemodynamic stability, with significantly less deviation from baseline Mean Arterial Pressure at 10 and 15 minutes into the procedure (p < 0.05). Furthermore, BIS values at the moment of eye-opening were significantly higher in Group P (88.4 ± 4.2) compared to Group S (82.1 ± 5.1; p = 0.021), suggesting a distinct emergence neurophysiology. The incidence of PONV was notably lower in the Propofol group (5.5 percent) compared to the Sevoflurane group (22.2 percent). Conclusion: Propofol target-controlled infusion facilitates significantly faster emergence and greater hemodynamic stability than Sevoflurane in patients undergoing flexible bronchoscopy. The pharmacokinetic independence of Propofol from pulmonary gas exchange offers a distinct physiological advantage in this specific patient population. These findings support the adoption of TIVA-TCI as the standard of care for optimizing throughput in interventional pulmonology.